Curcumin Induces Autophagy-mediated Ferroptosis by Targeting the PI3K/AKT/mTOR Signaling Pathway in Gastric Cancer - Zheng, Xin; Liu, Jun; Hu, Wei; Jiang, Bin; Zhou, Xin; Zhang, Min; Song, Ming (Turkish Journal of Gastroenterology, 2024)
Background/Aims: As a very common malignancy of the digestive system, the incidence and mortality rates of gastric cancer (GC) are increasing year by year. The critical role of ferroptosis in cancer development has been well-documented. The polyphenol compound curcumin shows prominent anti-tumor effects in multiple cancer types, including GC. However, whether curcumin participates in GC tumorigenesis by regulating ferroptosis remains unknown. Materials and Methods: Gastric cancer cells AGS and HGC-27 were treated with curcumin (0, 10, and 20 μM). Cell viability and death were evaluated through CCK-8 and LDH release assays. LC3B expression in cells was estimated through immunofluorescence staining. Intracellular ferrous iron (Fe2+), GSH, MDA, and lipid ROS levels were assessed by corresponding assay kits. The cellular levels of autophagy markers (ATG5, ATG7, Beclin 1, and LC3B), ferroptosis markers (ACSL4, SLC7A11, and GPX4), and phosphorylated (p)-PI3K, p-AKT, and p-mTOR were determined through western blotting. Results: Curcumin attenuated cell viability but stimulated cell death in GC cells. Curcumin enhanced autophagy in GC cells, as demonstrated by the increased levels of ATG5, ATG7, Beclin 1, and LC3B. Besides, curcumin upregulated iron, MDA, GSH, and ACSL4 levels while downregulated lipid ROS, SLC7A11, and GPX4 levels, suggesting its stimulation on ferroptosis in GC cells. Curcumin decreased p-PI3K, p-AKT, and p-mTOR levels in cells. Importantly, the ferroptosis inhibitor ferrostatin-1 overturned the impacts of curcumin on GC cell viability, death, and ferroptosis. Conclusion: Curcumin suppresses GC development by inducing autophagy-mediated ferroptosis by inactivating the PI3K/AKT/mTOR signaling. Cite this article as: Zheng X, Liu J, Hu W, et al. Curcumin induces autophagy-mediated ferroptosis by targeting the PI3K/AKT/mTOR signaling pathway in gastric cancer. Turk J Gastroenterol. 2024;35(8):625-633.